Large fractionation of calcium isotopes during cave-analogue calcium carbonate growth - Reynard, L; Day, C; Henderson, G (Elsevier, 2011)
We have measured δ44/42Ca of laboratory-precipitated calcite grown in an experimental setup that closely replicates stalagmite formation. Calcium solutions were dripped onto two different substrates in tightly-controlled conditions and calcite precipitated due to rapid CO2 degassing. With seeded glass slides as the substrate, we observe a Ca isotope ratio in the calcite which is ∼0.5‰ per amu lower than that in the growth solution. This fractionation is generally almost twice that observed in previously published calcite growth experiments and indicates a large kinetic effect on Ca isotopes in the stalagmite growth environment. The precipitate forming near the spot where the drip lands shows slightly greater solution-to-precipitate fractionation than calcite further from the drip reflecting a decrease in this kinetic fractionation as precipitation continues. We interpret these results in the context of the model of Fantle and DePaolo (2007) which involves surface entrapment of light Ca isotopes to decrease calcite δ44/42Ca, and depletion of Ca from the solution in the direct vicinity of the growing calcite to increase calcite δ44/42Ca. In the stalagmite setting, the second of these effects is minimized so that calcite Ca isotope ratios are unusually light. This interpretation suggests that stalagmite Ca isotope ratios should decrease with the saturation state of the drip water (i.e. with the growth rate of calcite). Ca isotopes might therefore allow reconstruction of surface entrapment of trace metals and isotopes more generally and might, for instance, allow an assessment of the appropriate relationship between oxygen isotope fractionation and temperature for periods of past growth in stalagmites.